CHARACTERIZATION OF THE FROST HEAVE DEFORMATIONS IN HIGH LATITUDE AND DEEP SEASONALLY FROZEN SOIL OF INNER MONGOLIA WITH SENTINEL-1 INSAR OBSERVATIONS - T. Qu; H. Zhang; F. Niu; X. Shi; Z. Li (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
Global warming in recent years led to significant permafrost degradation worldwide. Accurate monitoring and comprehensive characterization of the deformation process in seasonally frozen soil is of great importance for constructions in cold regions in China. This work concentrates on the deformation laws and spatio-temporal characteristics of frost heave in high latitude and seasonally frozen soil of Inner Mongolia with time series InSAR observations. With 101 Sentinel-1 descending scenes that covered more than three freeze-thaw cycles for the study area along Shiwei-Labudalin Highway, this study realized the characterization of the frost heave deformations in seasonally frozen soil, and the analysis of the influencing factors of the hydrothermal process with the help of temperature and moisture data from in-situ monitoring. Time series InSAR observations show that most parts of the highway show obvious deformation with a displacement rate of around 30–60 mm/yr. Especially, the deformation evolution in this seasonally frozen soil region changes with seasons, demonstrating a notable annual cyclical characteristic and seasonal activity. Moreover, time series in-situ monitoring data in deep underground boreholes not only further explains the deformation kinematics from InSAR observations, but also provide a better supplement for a more comprehensive mechanism understanding of frost heave deformations.